EDUCATION AND INDUSTRIAL REVOLUTION 4.0 - Delipiter Lase (Universitas Negeri Medan, 2019)
Abstract: Industrial Revolution 4.0 has brought changes in various aspects of human life. One of them is the education system. The problem is, what components of education are affected, and how to respond to these implications? This paper aims to explain changes and alignment that are required to be done in education so that the human resources produced by various educational institutions can compete and contribute globally. The type of research used is library research. The discussion shows that the development of current and future curricula must elaborate on the abilities of students in the academic dimension, life skills, and the ability to live together and think critically and creatively. Other invisible skills like interpersonal skills, global-minded citizens, and literacy of the media and information available. Also, the curriculum must be able to direct and shape students ready to face the industrial revolution era with an emphasis on the fields of STEM. Curriculum reorientation refers to ICT-based learning, the internet of things, big data and computerization, as well as entrepreneurship and internship; this needs to be a compulsory curriculum to produce skilled graduates in literacy, technology literacy, and human literacy aspects. The competencies that must be possessed by the teacher are educational competence, skill for technological commercialization, capability in globalization, expertise in future strategies, and counselor competence. In addition to these competencies, teachers also need to have skills and friendliness with technology, collaboration, creative and taking risks, having a good sense of humor, and teaching as a whole (holistic). The open learning platform is one way to be considered by the school and teacher in deciding how education and learning are held. Keyword: Industrial Revolution 4.0, Education 4.0 Abstrak: Revolusi Industri 4.0 telah membawa perubahan dalam berbagai aspek kehidupan manusia. Di antaranya, dalam bidang pendidikan. Masalahnya adalah, apa saja komponen pendidikan yang terkena terdampak, dan bagaimana merespons implikasi ini? Makalah ini bertujuan untuk menjelaskan perubahan yang harus dilakukan pada sistem pendidikan sehingga sumber daya manusia yang dihasilkan oleh berbagai lembaga pendidikan dapat bersaing dan berkontribusi secara global. Jenis penelitian yang digunakan adalah penelitian kepustakaan. Pembahasan menunjukkan bahwa pengembangan kurikulum saat ini dan masa depan harus melengkapi kemampuan siswa dalam dimensi akademik, keterampilan hidup, kemampuan untuk hidup bersama dan berpikir secara kritis dan kreatif. Keterampilan tak kasat mata seperti keterampilan interpersonal, berpikir global, dan literasi media dan informasi. Selain itu, kurikulum harus mampu mengarahkan dan membentuk siswa dengan penekanan pada bidang STEM. Kurikulum mengacu pada pembelajaran berbasis TIK, internet of things, big data dan komputer, serta kewirausahaan dan magang. Ini perlu menjadi kurikulum wajib untuk menghasilkan lulusan yang terampil di bidang literasi, literasi teknologi, dan literasi manusia. Kompetensi yang harus dimiliki oleh guru adalah educational competence, competence for technological commercialization, competence in globalization, competence in future strategies, and counselor competence. Selain kompetensi ini, guru juga perlu memiliki keterampilan dan sikap yang bersahabat dengan teknologi, kolaborasi, kreatif dan mengambil risiko, memiliki selera humor yang baik, dan mengajar secara holistik. Open Learning Platform dapat dipertimbangkan oleh sekolah dan guru dalam memutuskan bagaimana pendidikan dan pembelajaran diselenggarakan. Kata kunci: Revolusi Industri 4.0, Pendidikan 4.0